Good practices for physical restraint in intensive care units: integrative review - Gabriela Freitas dos Santos; Ester Góes Oliveira; Regina Cláudia Silva Souza
ABSTRACT Objectives: to describe the available evidence on indications, complications, care and alternative strategies in the use of physical restraint in adult patients in Intensive Care Units. Methods: an integrative review conducted in the LILACS, Nursing Database, Índice Bibliográfico Español en Ciencias de la Salud, Scopus and CINAHL databases and the PubMed portal, in the period from June to August 2018. Results: the final selection was of 19 articles, from which the indications, complications, care and alternative strategies were extracted. The studies were conducted between the years 2003 and 2018, with a predominance of the United States; they were mostly classified (58%) in level 6 evidence, being performed by nurses, with multi-professional participation of psychologists, pharmacists, physicians, and nurses. Conclusions: the most common practices regarding physical restriction were described, and the need for the elaboration and implementation of protocols on intervention to support decision making was observed.